Analysis of E-Money Acceptance among Young Generation in Denpasar City - Budiana Penindra, I Made Dwi; Wedagama, Dewa Made Priyantha; I Gusti Ngurah Priambadi; Komaladewi, Anak Agung Istri Agung Sri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The development of digital payment systems has encouraged the increased use of electronic money (e-money) in Indonesia, particularly among the young generation as digital natives. However, the level of acceptance and usage of e-money is not yet evenly distributed, including in urban areas such as Denpasar City. This study aims to analyze the factors influencing e-money acceptance among the young generation in Denpasar City using the Technology Acceptance Model (TAM) approach with 114 respondent. This study employed a survey method with purposive sampling targeting young e-money users in Denpasar City. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that perceived usefulness and perceived ease of use have a positive and significant effect on attitude toward using e-money, and attitude toward using significantly affects behavioral intention to use. These findings confirm that perceived benefits and ease of use are key determinants in shaping attitudes and intentions to use e-money among the young generation. This study provides practical implications for e-money service providers and policymakers in promoting digital payment adoption.